A drone diagnosis of the environmental quality of the restinga on the south coast of Brazil - Cesar Aparecido da Silva; Matheus Kopp Prandini; Alan D'Oliveira Correa (Ocean and Coastal Research)
Drones have proven to be versatile tools for scientific studies aimed at assessing the environmental quality of various ecosystems. This study diagnosed the restinga vegetation in the coastal municipality of Pontal do Paraná, in the state of Paraná, Southern Brazil. This vegetation, which extends over 21.72 km of the coastline of the municipality, was grouped into eight sectors to optimize 27 drone flight plans. The images obtained were transformed into orthomosaics and classified into eight classes, following the random forest classifier: herbaceous, shrubby, arboreal, sand, degraded area, irregular construction, water, and other. We observed 289.11 ha of restinga, of which 183.66 ha (63.5%) corresponded to conserved areas and 105.45 ha (36.5%), to a total degraded area with irregular constructions, vegetation suppression, and introduction of exotic species. Sectors 1 and 5 showed the lowest (8.19 ha) and highest (21.00 ha) values of degraded areas, respectively. Sectors 6 and 8 were the most critical: their degraded areas exceeded the conserved areas of restinga by 4.15 and 3.95 ha, respectively. The main causes of the degradation n  in this study refer to irregular occupation.  Drone images are a valuable tool for environmental management and vegetation analysis of difficult-to-access sites.